Mitochondrial peptides modulate mitochondrial function during cellular senescence - Kim, Su-Jeong; Mehta, Hemal H; Wan, Junxiang; Kuehnemann, Chisaka; Chen, Jingcheng; Hu, Ji-Fan; Hoffman, Andrew R; Cohen, Pinchas (Aging (Albany, NY.), 2018)
Cellular senescence is a complex cell fate response that is thought to underlie several age-related pathologies. Despite a loss of proliferative potential, senescent cells are metabolically active and produce energy-consuming effectors, including senescence-associated secretory phenotypes (SASPs). Mitochondria play crucial roles in energy production and cellular signaling, but the key features of mitochondrial physiology and particularly of mitochondria-derived peptides (MDPs), remain underexplored in senescence responses. Here, we used primary human fibroblasts made senescent by replicative exhaustion, doxorubicin or hydrogen peroxide treatment, and examined the number of mitochondria and the levels of mitochondrial respiration, mitochondrial DNA methylation and the mitochondria-encoded peptides humanin, MOTS-c, SHLP2 and SHLP6. Senescent cells showed increased numbers of mitochondria and higher levels of mitochondrial respiration, variable changes in mitochondrial DNA methylation, and elevated levels of humanin and MOTS-c. Humanin and MOTS-c administration modestly increased mitochondrial respiration and selected components of the SASP in doxorubicin-induced senescent cells partially via JAK pathway. Targeting metabolism in senescence cells is an important strategy to reduce SASP production for eliminating the deleterious effects of senescence. These results provide insight into the role of MDPs in mitochondrial energetics and the production of SASP components by senescent cells.